Model-independent study of structure in B+→D+ D- K+ decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2020)
The only anticipated resonant contributions to B+→D+D−K+ decays are charmonium states in the D+D− channel. A model-independent analysis, using LHCb proton-proton collision data taken at center-of-mass energies of √s=7, 8, and 13 TeV, corresponding to a total integrated luminosity of 9 fb−1, is carried out to test this hypothesis. The description of the data assuming that resonances only manifest in decays to the D+D− pair is shown to be incomplete. This constitutes evidence for a new contribution to the decay, potentially one or more new charm-strange resonances in the D−K+ channel with masses around 2.9 GeV/c2.
R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, G. Frau, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecná, B. Leverington, P. Li, H. Malygina, J. Marks, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, A. Zhelezov [und viele weitere]
Im Titel sind die Zeichen "+" und "-" hochgestellt
Gesehen am 02.02.2022